2016
DOI: 10.7759/cureus.918
|View full text |Cite|
|
Sign up to set email alerts
|

Hydration Status as a Predictor of High-altitude Mountaineering Performance

Abstract: Background: Hydration status is a controversial determinant of athletic performance. This relationship has not been examined with mountaineering performance.Methods: This was a prospective observational study of mountaineers who attempted to climb Denali in Alaska. Participants’ urine specific gravity (SG), and ultrasound measurements of the inferior vena cava size and collapsibility index (IVC-CI) were measured at rest prior to ascent. Upon descent, climbers reported maximum elevation gained for determination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Our results show that nearly half of the respondents drink 2-3 L of fluids per day in the mountains, while the rest of the respondents take in even smaller amounts of fluids per day (Figure 3), which can lead to dehydration and have a negative impact on acclimatization. A study by Ladd et al [24] based on two methods of measuring hydration status (urine specific gravity and ultrasound measurements of the inferior vena cava size and collapsibility index) found that about half of the surveyed climbers who had climbed Denali in Alaska were dehydrated. Water supply was monitored in a group of Italians and Nepalese during an expedition to the Himalayas, reaching 3099 ± 462 g/day and 3240 ± 310 g/day, respectively [28].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results show that nearly half of the respondents drink 2-3 L of fluids per day in the mountains, while the rest of the respondents take in even smaller amounts of fluids per day (Figure 3), which can lead to dehydration and have a negative impact on acclimatization. A study by Ladd et al [24] based on two methods of measuring hydration status (urine specific gravity and ultrasound measurements of the inferior vena cava size and collapsibility index) found that about half of the surveyed climbers who had climbed Denali in Alaska were dehydrated. Water supply was monitored in a group of Italians and Nepalese during an expedition to the Himalayas, reaching 3099 ± 462 g/day and 3240 ± 310 g/day, respectively [28].…”
Section: Discussionmentioning
confidence: 99%
“…High-altitude hypoxia increases fluid loss and contributes to dehydration, which reduces aerobic capacity in high-altitude conditions [23]. Optimal hydration can be limited by environmental conditions, but also by the time and fuel resources needed to prepare drinking water, sourced from the glacier [24]. Reduced thirst at high altitudes is another factor contributing to dehydration [25].…”
Section: Introductionmentioning
confidence: 99%
“…Extremely low humidity is a major health concern for climbers (Davies, E.D. et al 2016;Ladd, E. et al 2016) as -compounded by the high rate of respiration -it leads to the severe drying of the skin around the mouth and nose and the mucosal lining of the airways (Tsutsumi, H. et al 2007; Takada, S. and Matsushita, T. 2013). The dry mucosa of the larynx could produce a dry, hacking cough named high altitude bronchitis (Cogo, A. et al 2004;Ladd, E. et al 2016), and skin dryness could also lead to injuries of the epidermis.…”
Section: Low Precipitation and Humiditymentioning
confidence: 99%